UNITARY SYSTEM HYPOTHESIS AND DUAL SYSTEM HYPOTHESIS IN LANGUAGE DEVELOPMENT - Puspita Dewi (Humanitatis : Journal of Language and Literature, 2017)
Many countries throughout the world use more than one language such as English, Arabis, and Mandarin as their daily communication. In Indonesia, English as a foreign language becomes a compulsory subject in Junior High School and Senior High School. It shows that children or society are encouraged to learn and/or use more than one language that is called bilingual. Besides that, most parents support their children to learn English because they assume that English is able to shape a better future for their children. However, related to the theory, children who acquire two or more languages simultaneously will get confusion called the Unitary System Hypothesis. However, some scholars believe that acquiring more than one language at the same time will not undergo confusion for the children or it is called Dual System Hypothesis.